2018
DOI: 10.1097/md.0000000000011517
|View full text |Cite
|
Sign up to set email alerts
|

Change in lipoprotein-associated phospholipase A2 and its association with cardiovascular outcomes in patients with acute coronary syndrome

Abstract: Lipoprotein-associated phospholipase A2 (Lp-PLA2) probably plays an important role in the development of acute coronary syndrome (ACS). However, alterations of Lp-PLA2 levels during ACS and its association with cardiovascular outcome are unclear. Our aim was to investigate the change in Lp-PLA2 and its association with cardiovascular outcome in patients with ACS.A total of 79 patients with ACS came from the coronary care unit (CCU) between June 1, 2015 and August 31, 2016 in this longitudinal study. Serum leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Persson et al [24] observed that this enzyme was strongly correlated with lipid fractions and the degree of carotid artery atherosclerosis; this study showed that the association with cardiovascular risk is stronger for activity than for mass, reinforcing the impact of activity in atherogenesis [24]. Lp-PLA 2 , known as a novel inflammatory biomarker, is involved in the pathophysiology of atherosclerosis [5]. Lp-PLA 2 plays a role as a novel predictor of cardiovascular risk in a population at high risk for future CVD events [25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Persson et al [24] observed that this enzyme was strongly correlated with lipid fractions and the degree of carotid artery atherosclerosis; this study showed that the association with cardiovascular risk is stronger for activity than for mass, reinforcing the impact of activity in atherogenesis [24]. Lp-PLA 2 , known as a novel inflammatory biomarker, is involved in the pathophysiology of atherosclerosis [5]. Lp-PLA 2 plays a role as a novel predictor of cardiovascular risk in a population at high risk for future CVD events [25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 52%
“…Lipoprotein-associated phospholipase A2 (Lp-PLA 2 ), known as a novel inflammatory biomarker, is involved in the pathophysiology of atherosclerosis [5]. Lp-PLA 2 is produced by monocyte, macrophage and T lymphocytes on the atherosclerotic process [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These data highly suggest that the serum level of Lp-PLA2 in ACS patients has a certain clinical predictive value for the occurrence of MACEs within 6 months after discharge [23]. In Li et al study, Kaplan-Meier analysis showed that patients with elevated Lp-PLA2 had a lower cardiovascular event-free survival than those with lower Lp-PLA2.Meanwhile, Cox regression analysis of this study indicated that high Lp-PLA2 level, time delay from symptom onset to admission independently predicted cardiovascular event in patients with ACS after adjusting for potential confounders [24]. Maiolino et al reported that The survival without recurrent myocardial infarction rate was 81.2% in ACS patients with higher serum Lp-PLA2, which was significantly lower than that in ACS patients with lower serum Lp-PLA2.…”
Section: Prognostic Value Of Lp-pla2 In Patients With Chdmentioning
confidence: 49%
“…The simplest method of utilizing the Cox PH model was used by including the values of the longitudinal outcome at baseline (Time 0) (n = 7, 17.5%) [ 18 , 21 , 24 , 43 , 50 , 53 , 54 ]. For example, Tanne et al used baseline values of SBP to predict ischemic stroke mortality [ 53 ].…”
Section: Resultsmentioning
confidence: 99%